2013
DOI: 10.1111/echo.12417
|View full text |Cite
|
Sign up to set email alerts
|

Objective Measures of Right Ventricular Function during Exercise: Results of a Pilot Study

Abstract: The results of our pilot study suggest that sBEE might be promising for detecting RV abnormalities during exercise. A larger prospective study is now needed to determine if TAPSE and tricuspid annular systolic velocity recorded during sBEE might be useful in assessing patients presenting with dyspnea during exercise or suspected of having PAH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 53 publications
(64 reference statements)
0
10
0
Order By: Relevance
“…Prior work has shown that both tricuspid annulus plane systolic excursion (TAPSE) and tricuspid annulus systolic velocity (S’) are useful and reproducible measures of the longitudinal systolic function of RV. [ 16 ] Specifically, TAPSE was measured in the apical four-chamber view by aligning the M-mode cursor along the movement of the lateral TA to measure total basal to apical longitudinal excursion during ventricular systole. [ 11 12 17 ] The time interval from the lowest to the highest point was measured and will be referred to as the time-to-peak of TAPSE, as shown in Figure 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Prior work has shown that both tricuspid annulus plane systolic excursion (TAPSE) and tricuspid annulus systolic velocity (S’) are useful and reproducible measures of the longitudinal systolic function of RV. [ 16 ] Specifically, TAPSE was measured in the apical four-chamber view by aligning the M-mode cursor along the movement of the lateral TA to measure total basal to apical longitudinal excursion during ventricular systole. [ 11 12 17 ] The time interval from the lowest to the highest point was measured and will be referred to as the time-to-peak of TAPSE, as shown in Figure 1 .…”
Section: Methodsmentioning
confidence: 99%
“…The only significant changes observed were in the TAPSE. TAPSE is a reliable marker of global RV function, and correlates with right ventricular ejection fraction [15]. We found a modest but significant TAPSE decrease in the total group which is indicative of an increase of pulmonary arterial pressure.…”
Section: Discussionmentioning
confidence: 48%
“…Several validation studies have highlighted the correlation between TAPSE and RV function assessed by the biplanar Simpson’s rule,20 radionuclide angiography or cardiac MRI,21 and tricuspid excursion has been previously reported to have good predictive value for RV failure 22. With respect to other parameters of RV function, TAPSE is a simple and largely reproducible parameter which can be easily measured during ex-echo23 and therefore applied in everyday clinical practice (TAPSE can be measured later using anatomic M-mode modalities which makes this parameter more robust and realistic to measure than the other parameters).…”
Section: Discussionmentioning
confidence: 99%